Experiences gained in tackling the arsenic disaster: final report on arsenic mitigation project in Sonargaon and Jhikorgachha - Hossain, Md Zabed; Mahmud, Shah Noor; Jakariya, Md. (BRAC Research and Evaluation Division (RED), 2019)
This report describes the experiences gained in the "action research on community-based arsenic mitigation project" implemented by BRAC in Sonargaon and Jhikorgachha upazilas of Bangladesh. The project was implemented in two phases. The first phase of the project was implemented during the period from June 1999 to December 2001 . Experiences of the phase 1 have been described in BRAC report (Chowdhury et a!. 2000). After completion of the phase 1 of the project some further works and follow-up activities were carried out during January 2001 to December 2001. The objectives of the phase 11 of the project were to: (i) assess the present status of arsenic concentration in all green, cross and at least 10% of the red tubewells marked in Phase I; (ii) involve community members in choosing, financing, implementing, and maintaining alternative sources for safe drinking water; (iii) provide alternative safe \I'later options with active participation from the communities; (iv) identify arsenic affected patients in the project areas and provide treatment or referral whichever is appropriate; (v) make community people aware of dangers of arsenic poisoning; and (vi) develop a system involving local communities and local level officials in different phases of the project activities for the long-term sustainability of the safe water implementation plan. A total of 2(),058 tubewells, 10,062 from Sonargaon and IS,<)9() from .Jhikorgachha was selected for re-testing in the Phase 11. from the monitoring of the tube wells for more than two years it was found that there was no significant change in the concentration of arsenic in the tubewell water in both the project areas.